2013
DOI: 10.1002/jsfa.6080
|View full text |Cite
|
Sign up to set email alerts
|

Washing effects of limonene on pesticide residues in green peppers

Abstract: The data indicated that washing with a low concentration of limonene for 5 min was the optimal treatment for elimination of pesticide residues in green pepper, considering effect and treatment time as well as cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…The higher pesticide reduction efficiency was obtained from higher concentration of 6 and 8% at higher soaking time 15 min. The results were in agreement with Rasolonjatovo et al (), Lozowicka et al (), Lu, Shen, Sun, Zhu, and Liu (), Soliman (), Zohair (), Kin and Huat (). The results showed that the dimethoate and dichlorvos have been effectively reduced by 8% of ACE when compared to AAE for 15 min washing time.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The higher pesticide reduction efficiency was obtained from higher concentration of 6 and 8% at higher soaking time 15 min. The results were in agreement with Rasolonjatovo et al (), Lozowicka et al (), Lu, Shen, Sun, Zhu, and Liu (), Soliman (), Zohair (), Kin and Huat (). The results showed that the dimethoate and dichlorvos have been effectively reduced by 8% of ACE when compared to AAE for 15 min washing time.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, the terpenoids have great solvency effect if combined with a surfactant. It was previously reported that the combination of limonene and lecithin was effectively reduced the pesticides from green pepper (Lu et al, ).…”
Section: Resultsmentioning
confidence: 97%
“…In the literature, it was reported that washing with tap water, different detergents, salt solutions (NaCl), and vinegar (acetic acid) may decrease the chlorpyrifos pesticide in cabbage by between 10% and 70% [ 42 ]. Recently, another report demonstrated that washing with different concentrations of limonene caused 20%-90% loss of the chlorpyrifos residues in green peppers [ 21 ]. However, Burchat et al observed that washing did not significantly decrease the amounts of organophosphorus insecticides in carrots [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic cleaning for 20 min lowered pesticides by 49.8%–84.4% [ 20 ]. Washing with a low concentration of limonene for 5 min was the optimal treatment for elimination of pesticide residues in green pepper, considering the effect and treatment time as well as the cost [ 21 ]. Recently, Ling and coworkers observed that the cooking process may result in removal of chlorpyrifos residue in vegetables, more effective than washing [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This organic compound presents interesting applications in different fields such as cosmetics, food, pesticide applications and pharmaceutical industries [11][12][13][14][15]. Furthermore, d-limonene is a good candidate to be used as a (bio-)solvent in the design of novel agrochemical products, replacing more pollutant chemicals [16].…”
Section: Introductionmentioning
confidence: 99%